Aspirations and livelihood diversification in rural Africa - Jonas Guthoff; Chrispinus Mutsami; Martin Christoph Parlasca; Thomas Heckelei; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2024)
Many people in rural Africa still rely on smallholder agriculture as their main source of livelihood. Yet pursuing other economic activities beyond farming to diversify incomes becomes increasingly important. In this paper, we focus on the role of people's income aspirations in the process of diversification. We first show that in settings where wage employment opportunities are scarce, income diversification is linked to higher levels of income. We test the theoretical prediction that aspirations that are moderately ahead, but not too far ahead of one's current income level, serve as best incentives for future-orientated behavior, such as income diversification. We leverage unique household panel data from four African countries to test this hypothesis, finding strong and robust evidence of an inverted U-shaped relationship between income aspirations and indicators of income diversification. Our findings underpin the importance of behavioral factors as channels for economic development and poverty reduction.
Keywords: D91; I39; O12; Q12; 330; Aspirations; Income diversification; Household welfare; Poverty